Management of Infected Gap Nonunion of Shaft of Femur by Ilizarov Method - Rooshad Ahmad Muhammad; Omer Ali Rafiq Barawi (Advanced Medical Journal)
Background and objectives: Distraction osteogenesis is one of the discoveries of Ilizarov which can be used to fill the gap in long bones, control infection, stimulate osteogenesis and equalize the limb. A nonunion is said to have occurred once there is clinical and/or radiological evidence of cessation of fracture healing, usually after 6-8 months. A septic nonunion is defined as a nonunion complicated by local infection at the fracture site and in the surrounding tissues. The aim of this study was to evaluate the effectiveness of treating infected nonunion of femoral shaft by using Ilizarov method.